2009
DOI: 10.1111/j.1939-165x.2008.00098.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of destained cytology slides for the application of routine special stains

Abstract: Destaining does not appear to affect the results of routine special staining for cytologic specimens. Destaining before special stains may be a valuable diagnostic strategy when few slides are present or only stained slides are available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
29
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(30 citation statements)
references
References 25 publications
1
29
0
Order By: Relevance
“…Investigation of cytologic specimens obtained by fine‐needle aspiration (FNA) is the least invasive approach to obtain a diagnosis of disease . Cytomorphology, however, can provide only limited insights into the biology of a neoplastic disorder or the etiology of an infectious process.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Investigation of cytologic specimens obtained by fine‐needle aspiration (FNA) is the least invasive approach to obtain a diagnosis of disease . Cytomorphology, however, can provide only limited insights into the biology of a neoplastic disorder or the etiology of an infectious process.…”
Section: Introductionmentioning
confidence: 99%
“…Cytomorphology, however, can provide only limited insights into the biology of a neoplastic disorder or the etiology of an infectious process. It may be necessary to combine cytomorphology with specific disease markers to elucidate the underlying disease and collect predictive data . In contrast to histologic investigations, which allow for multiple tissue sections that can examine individual cells, repetitive impression smears and FNA of the same tissue can by no means reproduce the same composition of cells and tissue components .…”
Section: Introductionmentioning
confidence: 99%
“…Use of destained WG slides for rhodanine staining has not been described previously. The destaining protocol used in this study is similar to what has been previously reported for use with multiple and varied stain techniques . Using the destained slides, copper granules were identifiable after rhodanine staining and a cCu grade could be determined.…”
Section: Discussionmentioning
confidence: 96%
“…The destaining protocol used in this study is similar to what has been previously reported for use with multiple and varied stain techniques. 25 Using the destained slides, copper granules were identifiable after rhodanine staining and a cCu grade could be determined. When there was discordance between WG Rh cCu and Rh cCu grades, the WG Rh cCu grade was usually lower, suggesting a loss of sensitivity for copper content in WG-stained and destained slides.…”
Section: Discussionmentioning
confidence: 99%
“…Leaving unstained slides for HE staining and posterior cytograding is unnecessary and may even cause problems, not only because cytological samples often differ in cellularity and diagnostic material (it is not infrequent that after a good slide, the consecutive has hemodilution and non-representative material), but also because, at least in theory, other cells such as macrophages or less elongated fibroblasts can be misjudged as mast cells and their nuclei considered for cytograding. We have evaluated the use of special stains after destaining DQ stained smears 4 and found that most stains, including HE and TB rendered good results (Fig. 1).…”
mentioning
confidence: 99%